The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1469-7580.2007.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

HSP110, caspase‐3 and ‐9 expression in physiological apoptosis and apoptosis induced by in vivo embryonic exposition to all‐trans retinoic acid or irradiation during early mouse eye development

Abstract: Apoptosis is an essential physiological process in embryonic development. In the developing eye of vertebrates, three periods of developmental apoptosis can be distinguished: early, intermediate and later. Within the apoptosis pathway, caspases play a crucial role. It has also been shown that HSP110 may have a potential role in apoptosis.The aim of this research was to study the expression of HSP110, caspase-3 and -9 in physiological, retinoic-or irradiation-induced apoptosis during early eye development. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Given this information, the authors hypothesized that HSP110 played a role in the early stages of apoptosis, but did not offer a mechanism. This study was supported by the findings of Gashegu et al (2007), who observed that HSP110 was expressed before caspase-3 during development of the mouse eye, and suggested a pro-apoptotic role for HSP110 in caspase activation. Although several studies agree that HSP110 is involved at some level in apoptosis in the developing embryo, its exact role has not yet been clarified.…”
Section: Hsp110/105 Developmental Regulation and Involvement In Apoptsupporting
confidence: 86%
See 1 more Smart Citation
“…Given this information, the authors hypothesized that HSP110 played a role in the early stages of apoptosis, but did not offer a mechanism. This study was supported by the findings of Gashegu et al (2007), who observed that HSP110 was expressed before caspase-3 during development of the mouse eye, and suggested a pro-apoptotic role for HSP110 in caspase activation. Although several studies agree that HSP110 is involved at some level in apoptosis in the developing embryo, its exact role has not yet been clarified.…”
Section: Hsp110/105 Developmental Regulation and Involvement In Apoptsupporting
confidence: 86%
“…A possible role in apoptosis was suggested for mouse HSP105 during early development since this protein was observed specifically in cells undergoing programmed cell death in the interdigital regions of the limb tissue (Hatayama et al, 1997). This proposed apoptotic role was supported by recent data linking HSP110 expression to caspase-3 expression during mouse development (Evrard et al, 1999;2000;Gashegu et al, 2007).…”
Section: Hsp110 Mrna Accumulation In A6 Cellsmentioning
confidence: 82%
“…HSP105 might have a similar, but stress-specific, role acting on proteins necessary for activation of caspase-3, such as through upstream molecules such as GSK3. It is interesting to note that elevated HSP105 previously was found to be associated with activated caspase-3 during development [46][47][48]. Alternatively, the finding that knockdown of HSP105 reduced caspase-3 activation could be interpreted as indicating that HSP105 does not facilitate caspase-3 activation but instead suppresses an alternative death pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Sections were incubated at 4 ° C overnight with the following primary antibodies: anti-mouse PD-1 (clone 29F.1A12, rat IgG2a) for which specificity has previously been described 14 ; RGC markers anti-Brn3a (clone 5A3.2, mouse IgG1, Millipore/Chemicon) 15 and anti-NeuN (mouse IgG1, clone A60, Millipore/Chemicon) 16 ; amacrine cell marker anti-mouse AP2α (3B5, mouse IgG2b, Developmental Studies Hybridoma Bank) 17 ; or apoptotic cell marker rabbit anti-mouse activated caspase-3 (R&D Systems) 18 . For immunohistochemistry, the Rat IgG Vectastain ABC Kit, AEC substrate kit, and hematoxylin QS counterstain (Vector) were used according to product instructions.…”
Section: Methodsmentioning
confidence: 99%